KINETIKA BIOTRANSFORMASI SUKSINONITRIL OLEH Pseudomonas sp. - Sulistinah, Nunik; Sunarko, Bambang (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Succinic acid (HOOC(CH2)2COOH) is commercial compound that primarily used in food products. This compound also used in textile industry for colouring process, drugs industry, paint, pernist and photography slice. Succinic acid usually produced in industry by chemical reaction and produce cyanide acid as by product. The objective of this research was to study the utilization of Pseudomonas sp. in produce succinic acid and to characterize of involved enzymes. The results showed that the enzyme optimally produce in log phase. The production rate of succinic acid formation was 0,982 mM/ml.h with the decrease of substrate consumption was 1,235 mM/ml.h. The yield of succinic acid during 81 hours fermentation was 81%. The optimum pH, temperature, Km and Vran were 7, 27°C, 90 mM, and 0,0002 mM/ml.h.